THE SIGNIFICANCE OF MODERN LABORATORY DIAGNOSIS METHODS IN MEDICINE - Shernafasova Zuxra; Vivek Selvapriya; Seliyan Harihara Sudhan; Kudratova Zebo Erkinovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Laboratory studies are considered additional methods and are one of the most important parts of examining the patient. In a number of cases, laboratory test data are crucial for diagnosis. The results of additional studies largely depend on the correctness of patient preparation. Some studies are conducted on all patients without exception, individual studies are conducted strictly according to indications, depending on the diagnosis.